2007
DOI: 10.2353/ajpath.2007.070049
|View full text |Cite
|
Sign up to set email alerts
|

RAGE Expression in Rhabdomyosarcoma Cells Results in Myogenic Differentiation and Reduced Proliferation, Migration, Invasiveness, and Tumor Growth

Abstract: Activation of receptor for advanced glycation end products (RAGE) by its ligand, HMGB1, stimulates myogenesis via a Cdc42-Rac1-MKK6-p38 mitogen-activated protein kinase pathway. In addition, functional inactivation of RAGE in myoblasts results in reduced myogenesis, increased proliferation, and tumor formation in vivo. We show here that TE671 rhabdomyosarcoma cells, which do not express RAGE, can be induced to differentiate on transfection with RAGE (TE671/RAGE cells) but not a signalingdeficient RAGE mutant (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 67 publications
3
52
0
Order By: Relevance
“…15,23 Moreover, one study reported that RAGE expression in rhabdomyosarcoma reduced proliferation, migration, invasiveness and tumor growth, and functional inactivation of RAGE in L6 myoblasts resulted in increased proliferation and tumor formation in vivo. 19,24 These data are also consistent with our results and suggest that a decrease in RAGE signaling is associated with tumor progression. However, our observations are at variance with the data obtained with glioma, gastric cancer, colon cancer, biliary cancer, and human pancreatic carcinoma cells, in which a positive correlation was found between RAGE expression, tumor progression, and metastasis.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…15,23 Moreover, one study reported that RAGE expression in rhabdomyosarcoma reduced proliferation, migration, invasiveness and tumor growth, and functional inactivation of RAGE in L6 myoblasts resulted in increased proliferation and tumor formation in vivo. 19,24 These data are also consistent with our results and suggest that a decrease in RAGE signaling is associated with tumor progression. However, our observations are at variance with the data obtained with glioma, gastric cancer, colon cancer, biliary cancer, and human pancreatic carcinoma cells, in which a positive correlation was found between RAGE expression, tumor progression, and metastasis.…”
Section: Discussionsupporting
confidence: 82%
“…[11][12][13][14][15][16][17][18][19] We previously reported a change in RAGE expression according to the sequential change of liver tissue. 20 The RAGE expression was higher in the early or prestages of cancer than in the normal liver or advanced hepatocellular carcinoma (HCC).…”
mentioning
confidence: 99%
“…Extracellular factors, acting via cell-surface receptors, and adhesion molecules control cell proliferation arrest and differentiation of myoblasts through regulation of signalling pathways for the expression of muscle-specific transcription factors. This, in turn, coordinates the expression and activity of a cohort of factors that are responsible for phenotypic changes, including myoblast fusion into myotubes, the precursors of the mature myofibres [50]. Our data demonstrate the specific role of GTP as an enhancer of the myogenic process; indeed, the data in Fig.…”
Section: Discussionsupporting
confidence: 60%
“…Total Src, ERK1/2, p38 MAPK, Akt, and p65 NF-B were detected using a polyclonal anti-Src (1:1,000; Cell Signaling Technology), anti-ERK1/2 antibody (1:20,000; Sigma), a polyclonal anti-p38 MAPK antibody (1:2,000; Cell Signaling Technology), polyclonal anti-Akt (1:1000; Cell Signaling Technology), and a polyclonal anti-p65 NF-B antibody (1:1,000; Santa Cruz Biotechnology), respectively. Analysis of culture medium HMGB1 was performed as described (50). Briefly, culture media were clarified by centrifugation, added with 1/100 volume of 2% sodium deoxycholate, and subjected to precipitation with 1/10 volume of 100% trichloroacetic acid.…”
Section: Methodsmentioning
confidence: 99%